Evaluation of kidney biopsies in elderly patients - (:unkn) unknown (SPRINGER, 2019)
ObjectiveThe renal parenchymal disease spectrum in geriatric patients is similar to that in younger patients and can be controlled by appropriate treatment. We evaluated the clinicopathological features of kidney biopsies from geriatric patients.Materials and methodsOne hundred nine native kidney biopsies from older patients (>65years old) obtained from 2005 to 2014 were evaluated retrospectively. The specimens were inspected by the same pathologist in the same laboratory by light microscopy and immunofluorescence.ResultsThe mean age of the patients was 72.47.8years (range 65-90years), and 51.3% were female. The most frequent indication for kidney biopsy was proteinuria at the nephrotic level (56.8%). The most frequent histopathological diagnoses were focal segmental glomerulosclerosis in primary glomerulonephritis and secondary amyloidosis in secondary glomerulonephritis. The rate of major complications due to kidney biopsy was <1%.Result p id=Par4 Kidney biopsy is an effective and safe method of evaluating renal parenchymal diseases in older patients.
Keywords: Geriatric; Kidney biopsy; Glomerulonephritis; Complication; PERCUTANEOUS RENAL BIOPSY; OLDER-ADULTS; EXPERIENCE; SPECTRUM; DISEASE